DINAMIKA PENGAMBILAN KEPUTUSAN DALAM KONDISI TRADE-OFF PADA MAHASISWA PENDIDIKAN EKONOMI PERAIH BEASISWA BIDIKMISI - Astri Srigustini; Edi Fitriana Afriza (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
This study aimed at scrutinising the decision making of trade off students related to (Tuition Assistance for Deprived and Excellent Students) BIDIKMISI scholarship allocations. The decision was made based on each individual priority, reasonable selections and utility of scholarship users. Technically, descriptive qualitative method was deployed as the research design. The participants of this study were the Economic Education Department students at Siliwangi University. The data were collected through observation, interview, and document analysis. The findings demonstrated that most of scholarship allocations were utilised for fulfilling non-academic needs, notably 87%. Meanwhile, 13% of it were allocated for academic requirements. Viewed from the scholarship users’ perspectives, they preferred to select and employ scholarship for non-academic needs, such as entertainment and travelling instead of academic needs.